Ebû Hanîfe'nin Hukuk Düşüncesinde Farazî Fıkıh - Kılıç, Halil (Muş Alparslan Üniversitesi, 2021)
Islamic law, whose sources are based on revelation, in the first century AH, followed a fact-oriented course covering the period of sahabah and tabiun. At this stage, dealing with fiqh issues, they were not detailed, but jurists took place and made individual ijtihads on issues of actuality. However, this situation reversed in the second century. The conflict of the Iraqis and the Hijazis, in the expressing regional structuring, has been replaced by the ahl al ra’y and ahl al hadith schools, which express the difference in the method followed in achieving religious provisions. Abu Hanifa, who is the most important figure of the Ahl al ra’y that centered on Kufa, carried out an activity that would save the Islamic law from the independent issues and the dispersed structure of ijtihads belonging to these issues. Today, this activity, which is called "hypothetical fiqh" and expresses ijtihad about hypothetical issues that have not occurred, has been one of the actors that have transformed Islamic law into a doctrinal legal system. Although the first examples of hypothetical fiqh are found during and after the revelation period, Abu Hanifa has systematized this method by applying it to all fiqh issues. The issues created by Abu Hanifa with this method also influenced the development of other madhhabs. In Abu Hanifa's fiqh activities, hypothetical issues were used for many purposes. As he stated, hypothetical fiqh helps the jurist at the point of ensuring justice, since it is a future-oriented law construction. It provides a holistic perspective by providing the rational and logical pattern among fiqh topics. And allows the student to test his ability on hypothetical issues and to see his deficiencies in fiqh education. In this respect, the hypothetical fiqh has been beneficial to the practice of Islamic law and has become one of the pillars of the theoretical development of Abu Hanifa's legal thought as a sect.

Kaynakları vahye dayanan İslâm hukuku sahâbe ve tâbiûn dönemini kapsayan hicrî birinci asırda vakıa eksenli bir seyir izlemiştir. Bu evrede fıkıh konuları ele alınırken detaylandırılmıyor, fakîhler vuku bulmuş ve aktüalitesi bulunan meseleler hakkında bireysel içtihatlar yapıyorlardı. Ancak ikinci asırda bu durum farklı bir yönde gelişme göstermeye başlamıştır. Bölgesel yapılanmaları ifade eden Iraklılar ve Hicâzlılar ayrışması, yerini, şerî hükümlere ulaşmada takip edilen yöntem farklılığını ifade eden ehl-i re’y ve ehl-i hadîs ekollerine peyderpey bırakmıştır. Kûfe merkezli ehl-i re’yin en önemli siması olan Ebû Hanîfe, İslâm hukukunu, birbirinden bağımsız meselelerden ve bu meselelere ait içtihatlardan oluşan dağınık yapısından kurtaracak bir faaliyete imza atmıştır. Günümüzde “farazî fıkıh” olarak adlandırılan ve vuku bulmamış varsayımsal meseleler hakkında içtihadı ifade eden bu faaliyet, İslam hukukunun doktriner hukuk sistemine dönüşümünü sağlayan etkenlerden biri olmuştur. Farazî fıkhın ilk nüvelerine vahiy dönemi ve sonrasında rastlanıyorsa da Ebû Hanîfe, bu yöntemi bütün fıkıh konularına uygulayarak sistemleştirmiştir. Ebû Hanîfe tarafından bu yöntemle oluşturulmuş meseleler, diğer mezheplerin gelişiminde de etkili olmuştur. Ebû Hanîfe’nin fıkıh faaliyetlerinde farazî meseleler birçok amaçla kullanılmıştır. Kendisinin ifadesiyle farazî fıkıh, geleceğe yönelik bir hukuk inşası olduğundan, adaletin temini noktasında hukukçuya yardımcı olmaktadır. Fıkıh konuları arasında aklî ve mantıkî örüntüyü sağlayarak bütüncül bir bakış açısı sunmaktadır. Fıkıh eğitiminde öğrencinin varsayımsal meseleler üzerinde yeteneğini test etmesine ve eksik yönlerini görmesine olanak sağlamaktadır. Bu yönüyle farazî fıkıh, İslâm hukukunun pratikte uygulanmasına yarar sağladığı gibi Ebû Hanîfe’nin hukuk düşüncesinin bir mezhep olarak teorik gelişiminin sacayaklarından biri olmuştur.
Hypothetical Fiqh in Abu Hanifa's Thought of Law
dinbil
Keywords: Islamic law; Abu Hanifah; Ahl-i Re; hypothetical fiqh; ijtihad; islam hukuku; Ebû Hanîfe; ehl-i re'y; farazi fıkıh; içtihat